Designing fit-for-context climate change adaptation tracking: Towards a framework for analyzing the institutional structures of knowledge production and use - Njuguna, Lucy; Biesbroek, Robbert; Crane, Todd A.; Tamás, Peter; Dewulf, Art (Elsevier, 2022)
The Paris Agreement encourages countries to monitor and regularly report on their progress in responding to the impacts of climate change. So far, discussions on adaptation tracking have focused on the technocratic reasons for limited progress on adaptation tracking, for example, financial, methodological, and technical capacity gaps. Substantial variation exists in the institutional context within which adaptation takes place and is being tracked. Yet, recent discussions overlook the importance of the extent to which new systems of adaptation tracking fit within the prevailing rules and practices of knowledge production and use. Although such a fit-for-context approach has been considered important in other fields, no adequate frameworks exist to operationalize it within adaptation tracking. We develop a six-dimensional framework for analyzing institutional structures as the first step towards alignment in the design and use of adaptation tracking: 1) stakeholder participation, 2) transparency, 3) bureaucratic accountability, 4) engagement with experts, 5) politico-administrative relations, and 6) coordination within the administration. For each dimension, we synthesize academic literature, provide variables for operationalization, and provide examples drawn from various regions. The resulting framework allows the description of the institutional structures of knowledge production and use and supports the context-specific design of new programs, tools, and practices for tracking adaptation progress.